Broadband DVB-T2 Channels at a Physical Level – Simulation Analysis - Miskovic, Bozimir; Reljin, Irini (Elektronika ir Elektrotechnika, 2015)
Digital video broadcasting (DVB) decreases the proportion of broadcasting channels used for existing programmes. Second-generation DVB standards offer increased bit rates, enabling more programmes per broadcasting channel than in case of the first generation. On the other hand, increased bit rate needed for high definition programmes requires combining of the capacity of few single channels producing a broadband one. Also, statistical multiplexing allows more efficient usage of capacity. Terrestrial broadcasting standard DVB-T2 enables the time frequency slicing (TFS), as a way of connecting channels at the media access control (MAC) level. This paper deals with the two types of a broadband channels at physical layer. Compared to the TFS mode, method proposed here utilizes the allocated bandwidth in a more efficient way. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.5584